Aristolochic Acid Affects Upper Tract Urothelial Cancer Behavior through the MAPK Pathway - Chen, I-Hsuan (Molecules, 2019)
The prevalence of upper tract urothelial carcinoma (UTUC) in Taiwan is relatively higher than thatin Western countries. Aristolochic acid (AA), which is widely used in traditional Chinese herbology, is now recognized to be one of the carcinogens for UTUC. Numerous UTUC patients have chronic kidney diseases or end-stage renal diseases; however, little literature hasreported on theoncogenic pathway of AA-related UTUC. The aim of our study was to identify the potential target treatment for AA-related UTUC. Here, we established an AA pre-exposure followed bya 3-methylcholanthrene (MCA) stimulus tumorigenic cell model. We not only demonstrated that AA pre-exposure MCA stimulus tumorigenic cells have more behaviors of cell migration and invasion by enhancing the metalloproteinases (MMP) activity, which is compatible with clinical findings of AA-related UTUC, but we also validated that AA pre-exposure MCA stimulus tumorigeniccells could be activated through the mitogen-activated protein kinases (MAPK) pathway. We further dissected the route of the MAPK pathway and found that the p38 and extracellular signal regulated kinases (ERK) sub-pathways might play essential roles in AA pre-exposure urothelial cancer cell lines. This consequence was also corroborated with a tissue study in AA-exposed patients.